PENGARUH INTELECTUAL CAPITAL TERHADAP KINERJA KEUANGAN PADA KOPERASI SIMPAN PINJAM AR-ROHMAH JAWA TIMUR - Kafidin Muzakki (GREENOMIKA, 2020)
The cooperative as a lending institution also contributes to the microcredit market needed by the company in order to maintain its business. However, the number of cooperative developments in East Java every year is inconsistent due to the high level of competition. Intellectual Capital has a role in improving the company's financial performance so it is expected to help achieve the goals and success of the cooperative business. This research was conducted at the Ar-Rohmah Credit Savings Cooperative in East Java using an explanatory research model, with the results of the study showing that the variables forming intellectual capital consisting of human capital, structural capital, and employed capital contributed 66.5% to the company's financial performance . So it can be concluded that intellectual capital has a significant influence on financial performance in the Ar-Rohmah Jawa Timur Credit Savings and Cooperatives.